The Smart Home meets the Web of Things. (19th May 2011) - Kamilaris, Andreas; Pitsillides, Andreas; Trifa, Vlad
In recent years, the merging of computing with physical things, enabled the transformation of everyday objects into information appliances. We propose to reuse the central principles of the modern Web architecture to fully integrate physical objects to the Web and build an interoperable Smart Home. We present an application framework that offers support for multiple home residents concurrently. We show that by using the Web as application layer we can build flexible applications on top of heterogeneous embedded devices with only a few lines of code, transforming home automation into a trivial task. We address many issues related to Web-enabling these devices, from their discovery and service description to the uniform interaction with them. Our evaluation efforts indicate that our framework offers acceptable performance and reliability.